2019
DOI: 10.1002/term.2972
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in chemotherapy‐induced peripheral neuropathy: A new challenging approach that requires further investigations

Abstract: Chemotherapeutic drugs may disrupt the nervous system and cause chemotherapyinduced peripheral neuropathy (CIPN) as side effects. There are no completely successful medications for the prevention or treatment of CIPN. Many drugs such as tricyclic antidepressants and anticonvulsants have been used for symptomatic treatment of CIPN. Unfortunately, these drugs often give only partial relief or have dose-limiting side effects. Thus, the treatment of CIPN becomes a challenge because of failure to regenerate and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 173 publications
(177 reference statements)
0
13
0
1
Order By: Relevance
“…Studies have shown that MSCs may suppress the activity of B cells and reduce autoantibody production ( 18 ). In addition, they can promote the expansion of Tregs by secreting IL-10, IDO, and transforming growth factor beta (TGF-β) ( 19 , 20 ). Moreover, MSCs can suppress the differentiation and proliferation of Th cells and increase the suppressive proportion of B cells via IDO ( 21 , 22 ), and IFN-γ is the main inducer of IDO ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSCs may suppress the activity of B cells and reduce autoantibody production ( 18 ). In addition, they can promote the expansion of Tregs by secreting IL-10, IDO, and transforming growth factor beta (TGF-β) ( 19 , 20 ). Moreover, MSCs can suppress the differentiation and proliferation of Th cells and increase the suppressive proportion of B cells via IDO ( 21 , 22 ), and IFN-γ is the main inducer of IDO ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, MSC-based therapies may provide a new therapeutic strategy for patients suffering from CIPN. Combined therapy using 'traditional' pharmacological agents and MSCs might also be an interesting approach for CIPN prevention and treatment [157].…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
“…The dual phosphodiesterase 4B/7A inhibitors and TRPA1 channel antagonists (HC-030031) reduced tactile allodynia in an OIPN model with TNFα-lowering effect [ 168 ]. Combined therapy using “traditional” pharmacological agents and mesenchymal stem cells (MSCs) may also be important in the prevention and treatment of CIPN [ 203 ]. Based on the double action of OHP dosage in neuropathy and chemotherapeutic effect, some chemosensitizers such as cerulenin may enhance the therapeutic effects of OHP, and thus lower the OHP-induced neuropathy [ 204 ]; however, individual precision treatment strategies warrant further exploration [ 205 ].…”
Section: Chemotherapy-induced Peripheral Neuropathy Prevention and Treatment: Therapy Candidates For Oipnmentioning
confidence: 99%